Introduction. Issue 2 (April 2019) - BOWN, CHAD P.; MAVROIDIS, PETROS C.
Abstract : The WTO dispute settlement system has come under severe criticism in recent times, which does not seem, for now at least, to affect its relevance. In terms of output, 2017 was yet another bumper year. We review eight cases that constitute the 'last word' of the dispute settlement system: we review exhaustively all Appellate Body reports, as well as all un-appealed panel reports.